Interlanguage Errors in English Textbooks for Junior High School Students in Surakarta - Endang Fauziati (TEFLIN, 2003)
The present study deals with the English textbooks for Junior High School students. It is worth studying because they are marked with a significant number of errors both in the area of vocabulary and grammar. This research is to find proof that the English used is still at the level of interlanguage (IL). Theories on Error Analysis (EA) and Interlanguage (IL) have been used to analyze the data which consist of erroneous sentences taken from the reading texts only. The result reveals that the English used in the textbooks is still at the level of IL. The features of systematicity, permeability, and fossilization of an interlanguage also existed in it.